Strategi Otomatisasi Pemasaran Digital UMKM Melalui Pelatihan AI Dalam E-Commerce - Fatihanursari Dikananda; Nining Rahaningsih; Ridho Nugroho; Vicky Pamungkas (CV. Multi Kreasi Media, 2024)
The utilization of Artificial Intelligence (AI) offers significant potential for Micro, Small, and Medium Enterprises (MSMEs) to optimize their digital marketing strategies on e-commerce platforms. This Community Partnership Program is designed to provide training to MSMEs regarding the application of AI in various aspects of digital marketing. The training covers customer experience personalization, market data analysis, promotion content optimization, and improved online advertising efficiency. Through this activity, it is expected that MSMEs can enhance their understanding and skills in implementing AI-based solutions to expand market reach, improve customer interaction, and achieve more optimal digital marketing results in the e-commerce era.